Calibration of Scientific Educational Research Instruments Qualitative and Quantitative Approaches - Khoirina Badriyah; Halimatus Sa’diyah (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
Instrument calibration in scientific educational research plays an important role in ensuring the accuracy, consistency, and validity of the data obtained. This research discusses the instrument calibration process using a comprehensive qualitative and quantitative approach. The quantitative approach emphasizes testing the reliability and validity of instruments through statistical analysis, such as Cronbach's alpha coefficient for reliability and factor analysis for validity. Meanwhile, the qualitative approach involves an in-depth assessment of the quality of the items through interviews, observations, and initial testing to assess the relevance and understanding of respondents. Instrument adjustments were made based on the results of quantitative analysis and qualitative feedback, resulting in a more accurate and reliable instrument. This research shows that the integration of qualitative and quantitative approaches in the instrument calibration process can improve the quality of measurements and the overall validity of educational research results.